THE POTENTIAL OF BLOCKCHAIN TO ENHANCE EFFICIENCY AND TRACEABILITY IN THE SHIPPING PROCESS: A STUDY OF VEHRO’S SUPPLY CHAIN MANAGEMENT - Meivia Nisrina Effendi; Kees Tesselhof (Diponegoro Journal of Accounting, 2023)
In the age of globalization, people are now attempting to use new technology to improve the effectiveness and efficiency of their lives, particularly their enterprises. This study examines how blockchain technology can enhance Vehgro's supply chain's shipping efficiency. Vehgro is a Dutch company that specializes in organic food goods. The study looks into how blockchain fits into supply chain management and how it affects the shipping process and the information sharing among the parties involved. It examines how blockchain can improve administrative processes, stakeholder communication, data security, and traceability. The study aims to offer insights and recommendations for businesses engaged in routine shipping operations and other entities in the delivery system. Interviewing Vehgro representatives and blockchain experts is one of the qualitative data collection methods used in the research approach. To get conclusions, the data will be reviewed and merged. According to the research, blockchain may increase data accuracy, administrative procedures can be streamlined through smart contracts, and stakeholder cooperation and communication in the information sharing can all be improved and prevent the occurence of asymmetric information. The report suggests a hybrid blockchain strategy and highlights how crucial it is to solve issues with stakeholder consent and change management. Encouraging open communication, creating collaboration, and overcoming change resistance are recommendations for managing change. Through blockchain technology, Vehgro can boost transparency, dependability, and sustainability in its shipping operations, which will help create a more effective and durable supply chain.